STRATEGY IMPLEMENTATION: THE EFECT OF DECENTRALIZATION, PARTICIPATION IN BUDGET SETTING, AND MANAGERSâ ATTITUDE ON PERFORMANCE - Riyanto, Bambang (Journal of Indonesian Economy and Business, 2010)
The performance of a business unit, to a large extent, is determined by the quality of itsÂ strategy and how well the strategy is implemented. This study examines the effect ofstrategy implementation on performance. In particular, it investigates the extent to whichÂ the fit between two crucial strategic supporting systems, namely decentralization andbudget system, and managersâ attitude with the strategy of SBU on performance. It isÂ argued that the more consistent the level of decentralization, degree of participation in thebudget system and managersâ attitude with the SBU strategies, the higher the performanceÂ will be, and vice versa. Unlike most prior studies, the hypothesis was tested by adoptingÂ the system of fit approach. Responses from 75 divisional managers of 75 diversifiedÂ companies are analyzed. The results show that managers pursuing a strategy ofÂ differentiation (cost leadership) report high performance when they worked in highly (less)Â decentralized structures, are given more (less) opportunity to participate in the budgetÂ process, and had strongly positive attitude toward their jobs and their firms. TheseÂ findings are consistent with the basic premise of strategy implementation that different strategies should be supported with different configuration of organizational structure andÂ process to achieve optimal results.Keywords: strategy implementation, decentralization, participation, attitude, system of fit.